Annotated bird sighting list for winter 1980-1981 compiled by Robert K. Myers - Myers, Robert K.et al (1981)
An annotated list of birds sighted by Robert K. Myers and other members of the Waterloo Audubon Society. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed